Cutaneous viral infections associated with ultraviolet radiation exposure. Issue 2 (7th September 2020) - Zhao, Yayi; Amorrortu, Rossybelle P.; Fenske, Neil A.; Cherpelis, Basil; Messina, Jane L.; Sondak, Vernon K.; Giuliano, Anna R.; Schell, Michael J.; Waterboer, Tim; Pawlita, Michael; McKay‐Chopin, Sandrine; Gheit, Tarik; et al.
Abstract: The complex interplay between ultraviolet radiation (UVR) and cutaneous viral infections in the context of cancer etiology is challenging to unravel, given the limited information on the independent association between UVR and cutaneous viral infections. Using multiple biomarkers of infection with 24 types of cutaneous human papillomavirus (HPV) and 4 types of polyomaviruses (HPyV), we investigated cross‐sectional associations with recent UVR exposure, using skin pigmentation measured by spectrophotometer. Age‐ and sex‐adjusted associations between UVR and viral seropositivity, viral DNA present in eyebrow hairs (EBH) and skin swabs (SSW) were estimated using logistic regression. Beta‐HPV seropositivity was associated with viral DNA positivity in EBH (OR = 1.40, 95% CI = 1.05‐1.88) and SSW (OR = 1.86, 95% CI = 1.25‐2.74). Similar associations were observed for Merkel cell polyomavirus. Participants in the highest tertile of UVR exposure were more likely to be seropositive for beta‐HPV (OR = 1.81, 95% CI = 1.16‐2.38), and have beta‐HPV DNA in EBH (OR = 1.57, 95% CI = 1.06‐2.33) and SSW (OR = 2.22, 95% CI = 1.25‐3.96), compared to participants with the lowest tertile of UVR exposure. UVR exposure was positively associated with three different markers of beta‐HPV infection. Therefore, future studies of HPV associated KC development should address more directly the role of HPV and UVR exposure as potential co‐carcinogens. Abstract : What's new? Infection with cutaneous human papillomavirus (HPV) or human polyomavirus (HPyV), may influence risk of keratinocyte carcinoma, but it's not known what role ultraviolet radiation (UVR) plays. Here, the authors undertook the first epidemiological study to probe the association between these viral infections and UVR exposure. They used a spectrophotometer to quantitatively measure UVR exposure, and they tested for biomarkers of 24 different HPV types and 4 types of HPyV. People with the highest levels of UVR exposure were the most likely to test positive for beta‐HPV, in blood tests, in eyebrow hairs and in skin swabs.